Answer:
The graphed function is
![y = \frac{1}{2} x + 2](https://tex.z-dn.net/?f=y%20%3D%20%20%5Cfrac%7B1%7D%7B2%7D%20x%20%2B%202%20)
Step-by-step explanation:
We can simplify all of the functions and see which three of them are the same.
The first one is already simplified.
![f(x) = \frac{1}{5} x - 4](https://tex.z-dn.net/?f=f%28x%29%20%3D%20%20%5Cfrac%7B1%7D%7B5%7D%20x%20-%204)
The second one is also already simplified.
![\boxed { y = \frac{1}{2} x + 2 }](https://tex.z-dn.net/?f=%5Cboxed%20%7B%20y%20%3D%20%20%5Cfrac%7B1%7D%7B2%7D%20x%20%2B%202%20%7D)
The third one is also already simplified.
![f(x) = \frac{1}{2} x + 1](https://tex.z-dn.net/?f=f%28x%29%20%3D%20%20%5Cfrac%7B1%7D%7B2%7D%20x%20%2B%201)
The fourth one is
![y - 3= \frac{1}{2} (x - 2)](https://tex.z-dn.net/?f=y%20%20-%203%3D%20%20%5Cfrac%7B1%7D%7B2%7D%20%28x%20-%202%29)
Expand to get:
![y - 3 = \frac{1}{2}x - 1](https://tex.z-dn.net/?f=y%20-%203%20%3D%20%20%5Cfrac%7B1%7D%7B2%7Dx%20%20-%201)
Add 3 to both sides to get:
![y = \frac{1}{2} x - 1 + 3](https://tex.z-dn.net/?f=y%20%3D%20%20%5Cfrac%7B1%7D%7B2%7D%20x%20-%201%20%2B%203)
![\boxed { y = \frac{1}{2} x + 2 }](https://tex.z-dn.net/?f=%5Cboxed%20%7B%20y%20%3D%20%20%5Cfrac%7B1%7D%7B2%7D%20x%20%2B%202%20%7D)
The last option is
![y - 1 = \frac{1}{2}(x + 2)](https://tex.z-dn.net/?f=y%20-%201%20%3D%20%20%5Cfrac%7B1%7D%7B2%7D%28x%20%2B%202%29)
Expand to get:
![y - 1 = \frac{1}{2}x + 1](https://tex.z-dn.net/?f=y%20-%201%20%3D%20%20%5Cfrac%7B1%7D%7B2%7Dx%20%2B%201)
Add 1 to both sides to get:
![y = \frac{1}{2} x + 1 + 1](https://tex.z-dn.net/?f=y%20%3D%20%20%5Cfrac%7B1%7D%7B2%7D%20x%20%2B%201%20%2B%201)
This simplifies to
![\boxed { y = \frac{1}{2} x + 2 }](https://tex.z-dn.net/?f=%20%5Cboxed%20%7B%20y%20%3D%20%20%5Cfrac%7B1%7D%7B2%7D%20x%20%2B%202%20%7D)
The missing graph is shown in the attachment.